The Feasibility of Exploiting IEEE 802.11n for Addressing MAC Layer Overheads in UASNs. (3rd September 2014) - Sayakkara, Asanka; Lee, Sungwon; Kim, Dongkyun
Underwater acoustic sensor networks (UASNs) consist of remotely deployed sensor nodes under sea or other water environments. Due to the extreme limitations faced by radio signals under water, acoustic channels are utilized for communication in such networks. However, UASNs are challenged by the characteristics of underwater acoustic channels such as lower signal propagation speed and higher signal attenuation. On top of such a challenged physical medium, MAC schemes which are designed based on their terrestrial counter parts are required to add extra overheads to the communication channel wasting the limited network resources. MAC layer overheads such as bandwidth wastage for interframe spaces and contention for occupying physical medium put limitations to the maximum reachable throughput of UASNs. IEEE 802.11n has well defined various MAC and physical layer enhancements to overcome throughput barrier in wireless LANs which includes two frame aggregation schemes, namely, A-MPDU and A-MSDU. In this paper, we study the feasibility of applying those frame aggregations well defined in IEEE 802.11n for reducing MAC layer overheads in UASNs. Based on simulation studies, we evaluate that these frame aggregation schemes are applicable in UWSNs.